2012
DOI: 10.1039/c2dt12364a
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient solvent system containing functionalized diglycolamides and an ionic liquid for americium recovery from radioactive wastes

Abstract: Three room temperature ionic liquids (RTILs), viz. C(4)mim(+)·PF(6)(-), C(6)mim(+)·PF(6)(-) and C(8)mim(+)·PF(6)(-), were evaluated as diluents for the extraction of Am(III) by N,N,N',N'-tetraoctyl diglycolamide (TODGA). At 3 M HNO(3), the D(Am)-values by 0.01 M TODGA were found to be 102, 34 and 74 for C(4)mim(+)·PF(6)(-), C(6)mim(+)·PF(6)(-) and C(8)mim(+)·PF(6)(-), respectively. The extraction of Am(III) decreased with increasing feed acidity for all three diluents, indicating an ion exchange mechanism for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 47 publications
(70 reference statements)
3
59
0
Order By: Relevance
“…Recently, pillararene platform tethered with functional groups were reported by us to be a novel class of extractants for Ln/An separation [8]. In particular, three structurally different pillar [5]arene-based diglycolamides (P5DGA) were found to be highly efficient in extraction of trivalent actinides and lanthanides from aqueous acidic solution [9]. Our attempts to grow single crystals were unsuccessful.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, pillararene platform tethered with functional groups were reported by us to be a novel class of extractants for Ln/An separation [8]. In particular, three structurally different pillar [5]arene-based diglycolamides (P5DGA) were found to be highly efficient in extraction of trivalent actinides and lanthanides from aqueous acidic solution [9]. Our attempts to grow single crystals were unsuccessful.…”
Section: Introductionmentioning
confidence: 87%
“…Herein we present the results of a corresponding study to understand the nature of the bonding and structure of the Eu 3+ -pillar [5]arene-based diglycolamide complexes ( Fig. 1) in ethanol/water mixture and a comparative study was also carried out with the molecular identity like TODGA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the separation of these two elements is also possible by the use of tri-n-octylmethylammonium bis (2-ethylhexyl) phosphate and tri-n-octylmethylammonium bis (2-ethylhexyl) diglycolamate ionic liquids diluted in conventional diluents [110] . Moreover, the system selectively separates americium from uranium and plutonium [111] .…”
Section: Ionic Liquids In Extractionmentioning
confidence: 99%
“…selectively from a mixture containing U(VI), Pu(IV) and Pu(VI). 205 The ionic liquid was also used to test the behaviour of the calix [4]arenes with SHLW, showing promising results. 206 Further study of the ionic liquid system revealed that better extractions were obtained at low HNO3 concentrations, reverting the usual trend observed in apolar solvents, 207 and the Am(III) extraction profile of both-side DGA-functionalised calixarene CalixDGA-5 was independent of the acidity of the aqueous phase.…”
Section: Dgas On Platformsmentioning
confidence: 99%